A dichlorido-bridged dinuclear Dy(iii) single-molecule magnet with an effective energy barrier larger than 600 K. Issue 55 (20th June 2019) - Han, Tian; Ding, You-Song; Li, Zi-Han; Yu, Ke-Xin; Zhai, Yuan-Qi; Chilton, Nicholas F.; Zheng, Yan-Zhen
Abstract : A large energy barrier for magnetization reversal of about 623 K is observed in a dichlorido-bridged Dy(iii ) dimer. Abstract : We report a dichlorido-bridged dinuclear dysprosium(iii ) single-molecule magnet [Dy(Cy2 N)2 (μ-Cl)(THF)]2 which shows an effective energy barrier for magnetization reversal ( U eff ) of ca. 623 K. This is by far the largest U eff barrier for any chlorido-bridged lanthanide single-molecule magnet. We observe two relaxation processes with near-identical temperature dependencies, one of which disappears upon magnetic dilution. We suspect that these two processes are the isolated and coupled relaxation processes.